Effects of training distance on feed intake, growth, body condition and muscle glycogen content in young Standardbred horses fed a forage-only diet. (3rd April 2017) - Ringmark, S.; Revold, T.; Jansson, A.
Abstract : This study examined feed intake, growth, body condition, muscle glycogen content and nutrition-related health in 16 Standardbred horses fed a high-energy, forage-only diet ad libitum and allocated to either a control training programme (C-group) or a training programme with the high-intensity training distance reduced by 30% (R-group), from January as 2-year olds until December as 3-year olds. Feed intake was recorded on 10 occasions during 3 consecutive days. Body weight was recorded once in a week and height, body condition score (BCS), rump fat thickness and thickness of the m. longissimus dorsi were measured at 7±3-week intervals throughout the study. Muscle biopsies of the m. gluteus medius were taken in December as 2-year olds and in November as 3-year olds and analysed for glycogen content. Nutrition-related health disorders were noted when they occurred. Horses consumed 1.7% to 2.6% dry matter of BW, corresponding to 19 to 28 MJ metabolisable energy/100 kg BW. There were no differences between training groups in feed intake or any of the body measurements. The pooled weekly BCS was maintained between 4.8 and 5.1 (root mean square error (RMSE)=0.4). Muscle glycogen content was 587 and 623 mmol/kg dry weight (RMSE=68) as 2- and 3-year olds, respectively, and there was no difference between training groups. When managed under normal conditions, no nutrition-related health disorders or stereotypic behaviours were observed. It was concluded that the training programme did not affect feed intake, growth, BCS or muscle glycogen content. In addition, the forage-only diet did not appear to prohibit muscle glycogen storage, growth or maintenance of body condition, and seemed to promote good nutrition-related health.